The Effects of Taurine on Energy Homeostasis and Health: A Nutritional Perspective - Polat, İrem Dağoğlu; Baran, Özlem (My University, 2025)
Taurine is a sulfur-containing ?-amino acid that structurally differs from standard amino acids. It is found in high concentrations across various tissues of the human body and plays a role in numerous physiological processes, including antioxidant defense, energy regulation, and modulation of the central nervous system. Globally increasing obesity is accompanied by serious health problems such as metabolic syndrome, insulin resistance, dyslipidemia, and hyperglycemia. While traditional approaches have regarded adipose tissue as a passive structure solely involved in lipid storage, it is now recognized as an active endocrine organ. In this context, the biologically active molecules secreted by adipocytes and their roles in metabolic processes are critically important in the pathogenesis of obesity. The primary aim of this review article is to systematically evaluate the functional effects of taurine in adipose tissue and the mechanisms by which it counteracts obesity. Taurine possesses a structure that distinguishes it from typical amino acids and is present in high concentrations in the body, contributing to various biological functions such as reducing oxidative stress, suppressing inflammation, and regulating energy metabolism. Studies in animal models have demonstrated that taurine supplementation reduces inflammation in adipose tissue, increases lipolysis, activates thermogenic pathways, and suppresses appetite via central nervous system mechanisms, thereby preventing the development of obesity. Moreover, findings of low plasma taurine levels in individuals living with obesity and diabetes suggest that taurine deficiency may disrupt metabolic balance. Although animal and epidemiological studies indicate that taurine is promising for alleviating metabolic disorders, further advanced research is necessary to fully elucidate its mechanisms and confirm its efficacy in humans
Keywords: Obesity; Taurine; Adipose Tissue